2016
DOI: 10.1002/adem.201600033
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Processing Properties of Anatomic Facsimile Models (AFM) of the Temporal Bone with Original Human Bone Structures

Abstract: Due to a limited availability of human bone for training purposes in ear surgery, authentic models are needed. The Magdeburg temporal bone model (Mtbm) is an epoxy resin facsimile of a human os temporale which is manufactured by 3D printing based on human computed tomography data. Here, the processing properties of the Mtbm are investigated with respect to the drilling and milling behavior and the elastic modulus. Results are compared with those of human os temporale. The forces during drilling and milling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The materials have different mechanical properties, costs, and accessibility as some materials require more advanced print facilities. Five studies evaluated material suitability for replication of the human temporal bone 5,6,10,26,31 by testing flexibility and drilling behavior 6,31 and through subjective comparison with cadaveric or real-life temporal bones. 5,10,26 Three of these studies found resin well suited, 5,26,31 but a specific conclusion on which material is superior cannot be made (see Suppl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials have different mechanical properties, costs, and accessibility as some materials require more advanced print facilities. Five studies evaluated material suitability for replication of the human temporal bone 5,6,10,26,31 by testing flexibility and drilling behavior 6,31 and through subjective comparison with cadaveric or real-life temporal bones. 5,10,26 Three of these studies found resin well suited, 5,26,31 but a specific conclusion on which material is superior cannot be made (see Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies evaluated material suitability for replication of the human temporal bone 5,6,10,26,31 by testing flexibility and drilling behavior 6,31 and through subjective comparison with cadaveric or real-life temporal bones. 5,10,26 Three of these studies found resin well suited, 5,26,31 but a specific conclusion on which material is superior cannot be made (see Suppl. Tables S1 and S2 in the online version of the article).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have evaluated the most suitable material for replicating drilling of the bone [4,[15][16][17] and found resin to best mimic the hardness of the bone. However, this material requires using the more expensive photopolymerization printers and would increase the price per model, including the demand for manual post-processing as liquid residual material is entrapped in the mastoid air cells [12].…”
Section: Disagree Strongly Disagreementioning
confidence: 99%